Features of subjective factors of self-realization, depending on the specifics of tourism activities - Taissa Kyrylenko; Sophiya Pavelchuk (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The purpose of the article is to give the reader some information on the results of empirical research of self-identity and its determinants. The article describes the features of self-identity, depending on the specifics of tourism activities and level of involvement in such activities. The article analyzes the determinants of self-identity in tourist activities: emotional intelligence, rigidity, self-esteem, locus of control and five factors of personality.
Keywords: personal self-actualization; psychological determinants; tourist activity